Potentialities of Pilgrimage Tourism in Jammu and Kashmir UT, India (International Journal of Food and Nutritional Sciences, 2022)
Pilgrimage meaning travel for religious or spiritual purposes it motivates tourists for the achievement of religious attitude and practices. Pilgrimage tourism is considered to be one of the fast growing forms of tourism. This form of tourism is important for promoting inter faith harmony, love, affection and respect for each other’s religion, besides this promotes livelihoods which in turn increases living standard of people. .Jammu and Kashmir is the paradise on earth because of the great scenic beauty and sacred pilgrimage destinations which are very popular in India and all over the world. The paper will explore the phenomenon of pilgrimage tourism in the context of Jammu and Kashmir and will also highlight the major pilgrimage centers that are located in this state. The aim of the study was to determine what pilgrimage tourism is and how it is different from other forms of tourism, major pilgrimage centers and the issues and challenges in pilgrimage tourism in Jammu and Kashmir. The infrastructural issues at pilgrimage destinations are also highlighted in this paper.